PRELIMINARY RESULTS OF TOTAL KNEE ARTHROPLASTY: TASHKENT MEDICAL ACADEMY EXPERIENCE - Karimov, M.Yu.; Madrakhimov , S.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
Objective: to evaluate the short-term results of 82 patients who underwent primary total knee replacement (TKR), with an average follow-up period of 16 months. Material and methods: A prospective study was conducted in a multidisciplinary clinic of the Tashkent Medical Academy (Tashkent, Uzbekistan) and the Wiltse Memorial Hospital (Suwon, Republic of Korea). The sample consisted of 82 patients (54 women and 28 men) who underwent TKR from November 2018 to January 2020, with a total of 82 knee joints. The age of the patients ranged from 52 to 87 years (average age 61 years). The diagnosis of knee osteoarthritis of the 3rd – 4th degree (Kellgren and Lawrence) was confirmed in all patients. Several types of cement fixation implants were used (GruppoBioimpianti, DePuy, Corentec, Stryker, Zimmer). The Hospital for Special Surgery (HSS) scale, the volume of movements, and the visual analog pain scale (VAS) were used as criteria for functional evaluation. Results: The average duration of hospitalization was 11 days. The average volume of movements was 100.6° at the end of the observation period. The knee joint in all patients demonstrated adequate stability. All the patients returned to their former daily activities. 43 patients out of 52 patients in the 12-month postoperative period were satisfied with the outcome of the operation. During the study, there were no cases of postoperative mortality, periprosthetic infection and revision intervention. Conclusion: up to date, during clinical observation of patients with osteoarthritis of the knee joint who underwent primary TKR, the results were found satisfactory.